(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper aims to design and develop a new efficient toll collection system using QR Codes which will be a low cost alternative among all other systems. The system is based on Computer Vision vehicle detection using OpenCV library Java platform. In this system, a camera captures images of vehicles passing through toll booth thus a vehicle is detected through camera. On the other hand user generates a QR code for his vehicle and paste it on the windscreen of his vehicle. Depending on the area occupied by the vehicle, classification of vehicle is done as light and